KAJIAN TANGGAP PERTUMBUHAN DAN PRODUKSI TANAMAN KENTANG (Solanum tuberosum L.) PADA PEMBERIAN PUPUK NPK, PUPUK ORGANIK CAIR DAN TRICHOKOMPOS - Gabriel M. R. Sondakh; Edy F. Lengkong; Saartje Sompotan; Jemmy Najoan (Universitas Sam Ratulangi, 2020)
ABSTRACTPotatoes (Solanum tuberosum, L.) are one of the important food commodities after rice, maizeand wheat whose needs continue to increase both to meet domestic needs and even have the potential to beexported. This study aims to determine the effect of NPK fertilizer, Liquid Organic Fertilizer, andTrichocompost on the growth and production of potato (Solanum tuberosum L.). This study used aliterature study method, utilizing the results of research and scientific publications on the effect of NPKfertilization, Liquid Organic Fertilizer, and Trichocompost on the growth and production of potato plants.The results showed that the application of NPK fertilizer, Liquid Organic Fertilizer, and Trichokomposhad an effect on the growth and production of potato (Solanum tuberosum L.). The dose of NPK fertilizergiven to potato plants was 700 - 1,400 kg and could be combined with manure, with production 14.7 -22.5ton ha-1. The dose of liquid organic fertilizer can be given 5-25 ml / liter of water and can produce potatoproduction 23.13 - 34.56 ton ha-1. Tricho-compost biofertilizer can be given in solid form 25 ton ha-1 or inliquid form 5 ml / l -250 ml / l can be sprayed onto leaves or onto the soil, and can give potato production36.8 - 38.3 ton ha-1. Tricho-compost can help suppress and control the attack of soil-borne pathogens suchas Fusarium fungi, Phytophora fungi, and Phytium fungi which are important pathogens in potatocultivation..Keyword : potato, NPK, liquid organic fertilizer, trichocompost